GANDRUNG DANCE IN BANYUWANGI IN 1767 - 1974 - Ryndhu Puspita Lokanantasari; Nurmaria; Nandya Abror Nurmusabih (SOSIOEDUKASI, 2025)
Compulsive dance is an art that originated from Banyuwangi, an area located at the eastern tip of Java Island, which is inhabited by the Osing, Javanese, Madura and Balinese tribes. This article explains the history of compulsive dance by raising several main problems as follows; First, What is the background of the emergence of compulsive dance art in Banyuwangi?; Second, How is the development and function of the art of gandrung dance in Banyuwangi?. The research method in this article is the historical method. Based on the results of research, gandrung dance is an art that emerged in the colonial era, used as a means of indigenous communication to fight against the colonial government. Then after the independence era, gandrung dance has become a phenomenon and has its own attraction for the audience, because of the charm of its attractive and dynamic form of presentation. This charm and attraction has encouraged the local government and the people of Banyuwangi to support and develop the gandrung dance as a cultural characteristic of the Banyuwangi people. This has also shown that the art of gandrung dance in its development has changed from the colonial era to the independence era.